Telaah Hukum Positif Dan Hukum Islam Tentang Perkawinan Beda Agama - Dea Putri Ananda Tanggera Wahyu Sasmita (EL- Hayah, 2026)
This study examines the tension between positive law and Islamic law in responding to the phenomenon of interfaith marriage in Indonesia. Using a qualitative approach through literature study, this study analyzes livestock regulations based on Law Number 1 of 1974 concerning Marriage, Constitutional Court Decisions, and classical and contemporary Islamic jurisprudence views. This study focuses on the normative conflict between the principle of freedom of religion guaranteed by the constitution and the provisions on the validity of marriage according to religion, especially Islam. The findings show that positive law does not explicitly prohibit interfaith marriage, but its implementation is determined by the requirement of religious validation. Meanwhile, Islamic law provides strict limitations, especially regarding the prohibition of Muslim women from marrying non-Muslim men. This inconsistency creates administrative loopholes and legal gaps. This study also finds that a mediation approach, interfaith dialogue, and human rights-based regulatory reform can be constructive solutions in bridging religious values with social reality. Therefore, legal harmonization is very necessary in order to realize substantive justice for interfaith couples in Indonesia's pluralistic legal system.